Спростіть вираз а)3х-1/х-2 -5/х-2 б) a+b/a^2-ab+a-b/a^2+ab- 4a/a^2-b^2.

violetta238 violetta238    3   07.10.2019 09:38    0

Ответы
SkottHelimboorg SkottHelimboorg  10.10.2020 01:17

Объяснение:

(3х-1)/(х-2) -5/(х-2)=(3х-1-5)/(х-2)=(3х-6)/(х-2)=3(х-2)/(х-2)=3

(a+b)/(a^2 -ab) +(a-b)/(a^2 +ab) -4a/(a^2 -b^2)=(a+b)/(a(a-b)) +(a-b)/(a(a+b)) -4a/((a-b)(a+b))=((a+b)(a+b)+(a-b)(a-b)-4a^2)/(a(a-b)(a+b))=(a^2 +2ab+b^2 +a^2 -2ab+b^2 -4a^2)/(a(a-b)(a+b))=(-2a^2 +2b^2)/(a(a^2 -b^2)=-2(a^2 -b^2)/(a(a^2 -b^2))=-2/a

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра